Who Puts the 'Open' in Open Knowledge?. Issue 1 (23rd December 2020) - Montgomery, Lucy; Neylon, Cameron; Wilson, Katie; Huang, Chun-Kai (Karl); Hosking, Richard; Ozaygen, Alkim; Handcock, Rebecca
This paper explores the concept of 'open' knowledge – and the growing importance of digital literacies in supporting a transformation of universities into open knowledge institutions. In order to operate as successful open knowledge institutions, universities must do more than support the transmission of research outcomes from experts located within the university to external communities. They must engage in knowledge-making with communities. This involves questions of equity, diversity and inclusion – who gets to make knowledge; as well the role of productive interactions across boundaries (disciplines/university/wider community) in its growth and spread. There is a genuine desire among many universities, research funders, and researchers themselves, to address the challenges of diversity, equity and impact implicit in the open knowledge agenda. However, open knowledge aspirations are being stymied by comparative rankings that are built on data that excludes the work of entire disciplines, continents and languages; and are not capable of capturing important aspects of the value universities create. Many of the stakeholders using these rankings to inform decision-making are unaware of the prejudices and blind spots that current measurement tools create and perpetuate. They are also unaware that it is possible to interact critically with the tools used to measure and narrate performance; to demand that new questions are asked of the digital traces that universities and research communities create; and build better tools for understanding the role of universities in processes of knowledge-making and sharing. As this paper discusses, the Curtin Open Knowledge Initiative, a major research project funded by Curtin University, is a deliberate effort to support the new forms of digital literacy needed to enable this shift.